Analysis of the Utilization of Putri Cempo Landfill Waste for Power Plants and Their Effects on the Surakarta Electric Power Distribution Network - Suripto, Slamet; Hasibi, Rahmat Adiprasetya Al; Wiyagi, Rama Okta; Sanupal, Sanupal; Jusman, Yessi; Aribowo, Didik (Journal of Electrical Technology UMY, 2019)
Growth in electric energy demand, domination of use of fossil fuels, and waste problems are fundamental to this research. The purpose of this research is to find out the electrical energy potential of the Putri Cempo Landfill waste, Surakarta. The potential of electrical energy is designed for waste power plant (WPP). Penetration of WPP as a Distributed Generation (DG) to the 20 kV electrical distribution network is analyzed to determine its effect on the growth of demand for electricity, power flow, and the index of the (SAIFI and SAIDI). This research applies the technology Sanitary Landfill to produce landfill gas (LFG) as the primary energy of WPP. In calculating the growth predictions of electricity usage in the industrial, household, public, and commercial sectors from 2017 to 2025 in APJ Surakarta, the DKL Method 3.01 is applied. ETAP 12.6 was applied to analyze the power flow in the form of power losses and voltage losses and the Section method to calculate the reliability index (SAIFI, SAIDI) before and after penetration of WPP in PLR 01 and GDO 04 of Manahan Substation, Surakarta. The results showed that Trash from 5 Regencies and Cities, WPP was able to generate a maximum power of 10.1 MW. During peak load, WPP is able to reduce electricity demand of Substation for 0.920% in 2019, 0.879% in 2020, 0.838% in 2021, 0.799% in 2022, 0.760% in 2023, 0.723% in 2024, and 0.686% in 2025. The drop voltage at the tip of the feeder (No Substation Transformer BSP01005) has improved 29.4%, power losses have improved 25%, SAIFI has improved 61.36%, and SAIDI has improved 29%, after WPP penetration.